Vulnerability to Meningococcal Disease in Immunodeficiency Due to a Novel Pathogenic Missense Variant in NFKB1 - Anim, Manfred; Sogkas, Georgios; Schmidt, Gunnar; Dubrowinskaja, Natalia; Witte, Torsten; Schmidt, Reinhold Ernst; Atschekzei, Faranaz (Frontiers in Immunology, 2021)
NF-κB1 deficiency is suggested to be the most common cause of common variable immunodeficiency (CVID). NFKB1 encodes for the p105 precursor protein of NF-κB1, which is converted into the active transcriptional subunit p50 through proteasomal processing of its C-terminal half upon stimulation and is implicated in the canonical NF-kB pathway. Rare monoallelic NFKB1 variants have been shown to cause (haplo) insufficiency. Our report describes a novel NFKB1 missense variant (c.691C>T, p.R230C; allele frequency 0.00004953) in a family vulnerable to meningitis, sepsis, and late-onset hypogammaglobulinemia. We investigated the pathogenic relevance of this variant by lymphocyte stimulation, immunophenotyping, overexpression study and immunoblotting. The ectopic expression of p50 for c.691 C>T restricted transcriptionally active p50 in the cytoplasm, and immunoblotting revealed reduced p105/50 expression. This study shows that the deleterious missense variant in NFKB1 adversely affects the transcriptional and translational activity of NFκB1, impairing its function. Patients immunological parameters show a progressive course of hypogammaglobulinemia, which may partially account for the incomplete disease penetrance and suggest the need for closer immunological monitoring of those mutation carriers.